The impact of Cognitive Reserve in neuropsychological and functional abilities of Alzheimer's disease patients - Sobral, M.; Pestana, M. H.; Paúl, C. (Psychology and Neuroscience, 2015)
The concept of reserve, according to Stern (2009), has been proposed to account for the disjunction between the degree of brain damage or pathology and its clinical manifestations. There are two kinds of reserve that have been reported to make independent and interactive contributions to preserving function in the face of brain injury: Brain Reserve (passive model of reserve which is based on the quantity of available neural substrate) and Cognitive Reserve (active model of reserve) (Orueta, Bueno, & Lezaun, 2010; Steffener & Stern, 2012; Stern, 2013; Tucker & Stern, 2011, 2014). Cognitive Reserve (CR) is a hypothetical construct that has been used to inform of cognitive aging and describes the capacity of the adult brain to cope with the effects of the neurodegenerative process (Stern, 2009). CR is probably the result of innate intelligence (Álvarez & Rodrígues, 2004) or life experienced (Stern, 2013).